Analysis of fishers’ wellbeing in the western region of Ghana - Onumah, Edward Ebo; Al-Hassan, Ramatu Mahama; Ocran, Joseph; Béné, Christophe (Informa UK Limited, 2023)
Small-scale fisheries in Ghana are declining in response to the global fisheries crisis. The policies to curb this situation are dependent on the wellbeing of fishers in terms of material condition, quality of life, and transformative strategies for sustainable livelihoods. This paper employs survey data to investigate the wellbeing of fishers, using descriptives, principal-component analysis, and structural equation modelling. The results revealed that the summative effect of material condition, quality of life, and sustainability on fishers’ wellbeing is low. Despite the low ranking of income (lower among men fishers than women fish processors), basic necessities, and government support, fishers are still motivated to work but claim that their children may one day be locked out of the industry. This paper addresses the gap in the literature by establishing the need to enhance educational facilities for the children of fishers, while complementing with investments that create job opportunities in the fishing communities. This may eventually reduce dependence on the sea for sustainable fisheries.